Asymmetric simple exclusion process on a random comb: transport properties in the stationary state - Sarkar, Mrinal; Gupta, Shamik (Journal of statistical mechanics: theory and experiment, 2025)
We address the dynamics of interacting particles on a disordered lattice formed by a random comb (RC). The dynamics comprises that of the asymmetric simple exclusion process, whereby motion to nearest-neighour sites that are empty is more likely in the direction of a bias than in the opposite direction. The RC comprises a backbone lattice from each site of which emanates a branch with a random number of sites. The backbone and the branches run in the direction of the bias. The number of branch sites or alternatively the branch lengths are sampled independently from a common distribution, specifically, an exponential distribution. The system relaxes at long times into a nonequilibrium stationary state. We analyze the stationary-state density of sites across the RC, and also explore the transport properties, in particular, the stationary-state drift velocity of particles along the backbone. We show that in the stationary state, the density is uniform along the backbone and nonuniform along the branches, decreasing monotonically from the free-end of a branch to its intersection with the backbone. On the other hand, the drift velocity as a function of the bias strength has a non-monotonic dependence, first increasing and then decreasing with increase of bias. However, remarkably, as the particle density increases, the dependence becomes no more non-monotonic. We understand this effect as a consequence of an interplay between biased hopping and hard-core exclusion, whereby sites towards the free end of the branches remain occupied for long times and become effectively non-participatory in the dynamics of the system. This results in an effective reduction of the branch lengths and a motion of the particles that takes place primarily along the backbone.
Veröffentlicht: 30 May 2025
Gesehen am 15.09.2025